Integrating Google Classroom in Teaching: Changing the Learning Culture in Higher Education during a Pandemic - Ismail, Ismail; Mustakim, Mustakim; Samad, Ita Sarmita (Universitas Muhammadiyah Enrekang, 2021)
Technology integration is a benefit for students to learn differently to achieve goals and create the most important part of student life today. Google Classroom is a trend of blended learning in higher education that changes the strategy of delivering learning and teaching. The aim of this exploratory study is to investigate whether or not this application can be covered to develop or support learning in a Bachelor level of English Language Education program to facilitate student achievement. The test design was used to analyze student performance and the survey of perceptions of the use of Google Classroom was evaluated statistically using a questionnaire. The results revealed that students who participated in answering questions at the pretest found that there was no significant difference between the control group (45%) and also the experimental group (45.45%). In the posttest results, the two groups obtained an increase within the value of the final examination, however the contribution of 5th-semester students with the utilization of Google Classroom specifically benefited those with higher grades (81.82%) compared to third-semester students (70%). Moreover, the results of the student perceptions survey during this study indicate the use of Google Classroom is observed positively as a technology which will modernize dynamic learning and engagement, stimulate critical thinking and their participation if used suitably for learning functions.